A Novel Regulator PepR Regulates the Expression of Dipeptidase Gene pepV in Bacillus thuringiensis - Xin Zhang; Hengjie Wang; Tinglu Yan; Yuhan Chen; Qi Peng; Fuping Song (Microorganisms, 2024)
Bacillus thuringiensis produces insecticidal crystal proteins encoded by cry or cyt genes and targets a variety of insect pests. We previously found that a strong promoter of a DeoR family transcriptional regulator (HD73_5014) can efficiently drive cry1Ac expression in B. thuringiensis HD73. Here, we investigated the regulation of neighbor genes by HD73_5014. The HD73_5014 homologs are widely distributed in Gram-positive bacterial species. Its neighbor genes include pepV, rsuA, and ytgP, which encode dipeptidase, rRNA pseudouridine synthase and polysaccharide biosynthesis protein, respectively. The four open reading frames (ORFs) are organized to be a pepR gene cluster in HD73. RT-PCR analysis revealed that the rsuA and ytgP genes formed a transcriptional unit (rsuA-ytgP operon), while pepV formed a transcriptional unit in HD73. Promoter-lacZ fusion assays showed that the pepV and rsuA-ytgP promoters are regulated by HD73_5014. EMSA experiments showed that HD73_5014 directly binds to the pepV promoter region but not to the rusA-ytgP promoter region. Thus, the HD73_5014 transcriptional regulator, which controls the expression of the dipeptidase pepV, was named PepR (dipeptidase regulator). We also confirmed the direct regulation between PepR and PepV by the increased sensitivity to vancomycin in ΔpepV and ΔpepR mutants compared to HD73.